Tuberculosis and Diabetes Mellitus in Northwest of Iran - Ozma, Mahdi A.; Rashedi, Jalil; Poor, Behroz Mahdavi; Vegari, Ali; Asgharzadeh, Vahid; Kafil, Hossein Samadi; Kazemi, Abdolhassan; Sahebi, Leyla; Asgharzadeh, Mohammad (Infectious Disorders - Drug Targets, 2020)
Background: Planning for control of tuberculosis would need to screen and identify individuals susceptible to TB. Due to the weakness of immune system in diabetic patients, it is more likely for them to reactivate latent TB infection. Regarding the increasing number of diabetics in the community, in this study efforts have been made to estimate the frequency of individuals who have tuberculosis and diabetes mellitus (TB-DM) simultaneously, as it could help making preventive decisions to reduce TB in this part of Iran. Materials and Methods: In this study, 329 cases of confirmed TB patients were divided into two groups of diabetic and non-diabetic, then demographic information and clinical variables have been compared between the two groups. Results: Among the examined subjects, 47 patients (14.29 %) had suffered from diabetes mellitus and tuberculosis. All of the DM patients had pulmonary tuberculosis and 87.23% of them were over the age of 50. Conclusion: Majority of DM-TB patients were over 50 years of age and also more than half of them were women. So it seems that for DM women over the age of 50, to detect tuberculosis, screening tests such as PPD may be necessary.
Keywords: association